Dampak Konflik Israel-Palestina terhadap Niat Beralih (Switching Intention) pada Pembelian Konsumen: Pendekatan Push-Pull-Mooring - Usnan, Usnan; Indarta, Ahmad; Hasyim, Fuad (Jurnal Ilmiah Ekonomi Islam, 2024)
The Israel-Palestine conflict has sparked a boycott movement against Israeli products in Indonesia, particularly among pro-Palestinian consumers. This study aims to analyze the impact of push, pull, mooring, and sentiment variables on consumers' switching intention. The research employs the Push-Pull-Mooring (PPM) model approach. Data were collected through questionnaires using a simple random sampling technique and analyzed using Partial Least Square Structural Equation Modelling (PLS-SEM). The results indicate that push and pull factors increase consumers' switching intention, while mooring factors decrease it. Additionally, consumer sentiment towards the Israel-Palestine conflict significantly influences switching intention, both directly and as a moderator. This study contributes by integrating sentiment variables into the PPM theory, providing new insights into the influence of ethical, moral, and emotional factors on purchasing decisions. Recommendations include the importance of ethical marketing strategies and further research in countries with different socio-political contexts.